TINJAUAN PENERAPAN CRITICAL PATH METHOD (CPM) DAN PROGRAM EVALUATION AND REVIEW TECHNIQUE (PERT) DALAM PEMBANGUNAN PROYEK GEDUNG - Ningtyas, Rena Avinika; Yulistian, M Bagus; Pelu, M Rijali Sukur; Pranoto, Oktavianus; Daffarel, Rakyan Choiruna; Rahmayeni, Yuliza P; Putra, Okri Asfino (Politeknik Negeri Jakarta, 2025)
Infrastructure serves as a fundamental public service provided by the government to meet community needs, with its development significantly impacting societal welfare. Project delays and instability often result from inadequate planning. This research aims to evaluate the effectiveness of applying the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT) in determining the construction duration of the Building X project. Both methods are project management tools designed to improve time efficiency in construction activities. Calculations were performed using data provided by field personnel. While CPM utilizes a single time estimate, PERT incorporates three-time estimates to account for variability. The outputs of this study include the total duration required to complete the project and the identification of its critical path. Based on the analysis, the CPM method estimated a project duration of 37 weeks, whereas the PERT method estimated 38 weeks.